2019
DOI: 10.1021/acs.iecr.9b02030
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Adsorption Capacity by Alkoxy Groups: A Study on Acetic Acid Adsorption on UiO-66 Analogues from Aqueous Solution

Abstract: A series of alkoxy groups are introduced to the UiO-66 structure to enhance its adsorption performance toward acetic acid in water. The adsorption kinetics, isotherm, thermodynamics, and regeneration of these adsorbents have been investigated, and the excellent adsorption capacity of n-propyloxy-substituted adsorbent (UiO-66-3) is illustrated. The adsorption of acetic acid on UiO-66-3 was a complex multistep process, and the close contact between O of the ether bond of the adsorbent and H of the carboxyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…At present, a variety of adsorbents have been reported for acetic acid. Xianghai Guo et al used different kinds of water-tolerable metal-organic frameworks to systematically study the adsorptive activities for dilute acetic acid solutions, like MIL-derived and UiO-66-derived materials (Zhang et al 2016;Yu et al 2019). However, the high cost, the difficulty in large-scale industrial production, poor thermal and chemical stability make MOFs materials have many restrictions on industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a variety of adsorbents have been reported for acetic acid. Xianghai Guo et al used different kinds of water-tolerable metal-organic frameworks to systematically study the adsorptive activities for dilute acetic acid solutions, like MIL-derived and UiO-66-derived materials (Zhang et al 2016;Yu et al 2019). However, the high cost, the difficulty in large-scale industrial production, poor thermal and chemical stability make MOFs materials have many restrictions on industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies have been published on the adsorption of acetic acid. Guo and Chen’s research group reported a method of using MOF material UiO-66 to adsorb acetic acid in an aqueous solution [ 4 , 5 , 6 ]. Yang et al prepared an alkaline site-modified MgO for the selective adsorption of the CH 3 COOH/C 6 H 6 binary mixture, and their results show the highest selectivity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%